STRATEGI PENINGKATKAN MUTU PERGURUAN TINGGI AGAMA KATOLIK MELALUI TRANSFORMASI MANAJEMEN SUMBER DAYA MANUSIA - Hamu, Fransiskus Janu (SEPAKAT-Jurnal Pastoral Kateketik, 2016)
The purpose of this paper is to examine the situation and condition of theCollegeâs Catholic religion. Based on observations and experiences as a personwho was involved in organizing the Catholic religion, the College encouragesauthors to offer the concept of management development College Catholicreligion with a focus on the development of the human resource managementof College Catholicism. The author believes that human resources be onedetermining factor of a collegeâs quality.